Can an Aging Leopard Change Its Spots? The Role of Mindset of Aging on Implicit and Explicit Attitudes in Older Adults. (March 2023) - Brown, Kellie E.; Hall, Anna; Hillebrant-Openshaw, Madisen; Fulton, Erika K.
Growth mindset of aging (MA) refers to the belief that aging processes are malleable, while fixed MA is the belief that how one ages is predetermined and unchangeable. Using experimental methods, we manipulated MA and explored its impact on implicit old-age attitudes and self-perceptions of aging. Eighty-six older adults were randomly placed into a growth or fixed MA condition. Next, we assessed implicit old-age attitudes and self-perceptions of aging. The experimental manipulation was successful in that group MA scores differed, but MA did not significantly influence implicit old-age attitudes or self-perceptions of aging. However, a regression analysis revealed a novel finding: More growth MA was related to less negative implicit old-age attitudes and more positive self-perceptions of aging. These findings are an important contribution to the MA literature, which is in its infancy.